2021
DOI: 10.18421/tem101-33
|View full text |Cite
|
Sign up to set email alerts
|

Improving Aviation Insurance System in Russia

Abstract: The article is devoted to the study of aviation insurance system in Russia. The novelty is the presentation of aviation insurance as a system of elements. Within the framework of the study, the ranking of insurance companies by indicators of financial stability was carried out on the basis of the methodology proposed by Sberbank. The most stable company is National Insurance Group. An important result is the comparative analysis of aviation industry and aviation insurance industry in the period before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Anwar et al [ 20 ] found that greenfield transportation investment and sustainable energy mix helpful to reduced transportation embodied carbon emissions that is important to the way forward towards sustainable development goals. Finally, the impact of positive and negative shocks of IFS on carbon damages is negative in the long run, which reinforced the capability of green insurance schemes and sustainable financing options to mitigate carbon losses related to transportation in a country [ 70 , 71 ]. The error correction term shows the convergence of the estimated model in the short run, with a high speed of adjustment towards equilibrium over a while.…”
Section: Resultsmentioning
confidence: 99%
“…Anwar et al [ 20 ] found that greenfield transportation investment and sustainable energy mix helpful to reduced transportation embodied carbon emissions that is important to the way forward towards sustainable development goals. Finally, the impact of positive and negative shocks of IFS on carbon damages is negative in the long run, which reinforced the capability of green insurance schemes and sustainable financing options to mitigate carbon losses related to transportation in a country [ 70 , 71 ]. The error correction term shows the convergence of the estimated model in the short run, with a high speed of adjustment towards equilibrium over a while.…”
Section: Resultsmentioning
confidence: 99%